2016
DOI: 10.1097/md.0000000000004410
|View full text |Cite
|
Sign up to set email alerts
|

High efficacy of gemifloxacin-containing therapy in Helicobacter Pylori eradication

Abstract: Background:Helicobacter pylori (H pylori) is a common gastric pathogen which is associated with chronic gastritis, peptic ulcer, and gastric cancer. It has worldwide distribution with higher incidence in developing countries. Gemifloxacin is a fluoroquinolone antibiotic with documented in vitro activity against H pylori. Considering that there is no clinical data to verify gemifloxacin efficacy in H pylori eradication, this pilot clinical trial was designed.Methods:This prospective pilot study was performed du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…Our study revealed that 50.2% of our population were H. pylori positive, which was lower and at the same time higher compared to local and international studies. H. pylori infection causes a spectrum of both gastric and extra gastrointestinal diseases with acute and chronic gastritis, peptic ulcer disease, gastric atrophy, intestinal metaplasia, MALT lymphoma, and gastric adenocarcinoma 21…”
Section: Discussionmentioning
confidence: 99%
“…Our study revealed that 50.2% of our population were H. pylori positive, which was lower and at the same time higher compared to local and international studies. H. pylori infection causes a spectrum of both gastric and extra gastrointestinal diseases with acute and chronic gastritis, peptic ulcer disease, gastric atrophy, intestinal metaplasia, MALT lymphoma, and gastric adenocarcinoma 21…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it has been reported that stool antigen test is a sensitive and specific mean to diagnose and screen the H. pylori infection (15). Different therapeutic regimen for eradication of H. pylori has been suggested due to antibiotic resistance of this infection (6,16).…”
Section: Introductionmentioning
confidence: 99%
“…In agreement with these findings, a high‐efficiency eradication rate (≥90% PP cure rate) is documented for gemifloxacin‐containing quadruple therapy regimens, which recommend it as a component of second‐line treatment. The abovementioned findings can be in part explained by our study, which demonstrated better overall interactions of MXN and GXN, in comparison with LVX, on mutated H pylori GyrA.…”
Section: Discussionmentioning
confidence: 99%